Association of MTHFR C677T and A1298C polymorphisms with hypertension among Saudi subjects from Qassim region - Algahsham, Abdullah; Settin, Ahmad A A; Ali, Ahmad; Ismail, Hisham; Ismail, Hisham (International Journal of Health Sciences, 2012)
Objectives. To check for the association of genetic polymorphisms related to the methylenetetrahydrofolate reductase (MTHFR) gene namely C677T and A1298C with hypertension in Saudi affected subjects from Qassim region. Subjects and methods: Participants included 123 Saudi hypertensive cases (83 males and 40 females) in addition to 250 (142 males and 108 females) unrelated healthy controls from the same locality. Their age mean Â±SD was 50.93 Â± 15.43 years. For all subjects, DNA was extracted followed by real-time PCR amplifications for characterization of genotypes and alleles related to MTHFR C677T and A1298C gene polymorphisms Results: Total cases showed significantly higher carriage rate for the mutant allele 677T compared to controls (40.7% vs. 26%, OR=1.9, 95% CI= 1.2-3.1) with a lower frequency of the wild type 677CC genotype (59.3% vs. 74%, p=0.004). The same was observed among cases-subgroups of hypertension associated with obesity with a notably higher odds ratio (OR=2.6, 95% CI=1.3-5.01, p=0.004). Total cases showed also significantly higher frequency of mutant 1298 C allele carriage rate compared to controls (59.3% vs. 42.4%, OR=1.98, 95% CI= 1.3-3.1) with a lower frequency of the normal AAÂ genotype (40.7% vs. 57.6%, p=0.003). The same was observed among cases-subgroups of hypertension associated with both diabetes and obesity and among cases of hypertension with obesity, also with higher odds ratio (OR=2.6 and 2.2 respectively). Conclusion: This work showed that genetic polymorphisms related to the MTHFR gene are associated with the risk of hypertension particularly when accompanied with obesity and diabetes among Saudi subjects. Keywords: Methylenetetrahydrofolate reductase, hypertension, Saudi, Genetic polymorphisms